A guide for educational policy governance: effective leadership for policy development - Norton, M. Scott (The Rowman & Littlefield Publishing Group, 2017)
"M. Scott Norton is a former public school teacher, coordinator of curriculum, assistant superintendent, and superintendent of schools. He has served as professor and vice-chair of the Department of Educational Administration at the University of Nebraska at Lincoln and as professor and chair of the Department of Educational Administration and Policy Studies at Arizona State University, where he is currently professor emeritus"--